2011
DOI: 10.1111/j.1365-2648.2011.05854.x
|View full text |Cite
|
Sign up to set email alerts
|

The next of kin of older people undergoing haemodialysis: a discursive perspective on perceptions of participation

Abstract: The dominant part of the discourse as expressed by the next of kin seems to be a paternalistic ideology. Thus, finding ways to enable the next of kin to participate in the decision-making process seems to be a major challenge for the healthcare team in the dialysis units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
2
28
0
3
Order By: Relevance
“…In the hospital setting, informal caregivers struggle to be more involved [52]; however, participation can be hampered by a lack of dialogue between formal and informal caregivers [52,53]. Furthermore, research has shown that informal caregivers can act as a “bridge” between the patient and formal care, facilitating formal care [54] by initiating the process of acquiring formal help for their home-bound older relatives [37].…”
Section: Introductionmentioning
confidence: 99%
“…In the hospital setting, informal caregivers struggle to be more involved [52]; however, participation can be hampered by a lack of dialogue between formal and informal caregivers [52,53]. Furthermore, research has shown that informal caregivers can act as a “bridge” between the patient and formal care, facilitating formal care [54] by initiating the process of acquiring formal help for their home-bound older relatives [37].…”
Section: Introductionmentioning
confidence: 99%
“…Aasen et al described how the next of kin of elderly patients on hemodialysis "must struggle with both the patients and the health team to be included in the decision-making process." (29) Family members and friends enrolled in our study described similar struggles to be involved in the patients' care, but also spoke of situations in which their involvement was more or less expected by providers on the basis of health care system needs. Some described being caught in the middle between the patient and the health care system and even pitted against the patient (30,31,(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 89%
“…(25) This sentiment is echoed in more recent qualitative studies describing the experiences and perspectives of caregivers and family members of patients with advanced kidney disease as they pertain to specific treatments (e.g., hemodialysis, supportive care) (26)(27)(28)(29)(30)(31), advance care planning (ACP) (32), and end-of-life care (33)(34)(35). To our knowledge, no prior studies have attempted to characterize more broadly the experiences of family members and friends of patients with advanced kidney disease.…”
Section: Introductionmentioning
confidence: 99%
“…Para los hombres la pérdida del trabajo y dejar de ser proveedores para sus familias La metamorfosis también se presenta en las relaciones con amigos y colegas llevando al aislamiento (19,45), descrito e interpretado en los estudios como una forma de mantener la enfermedad en la esfera más privada, por temor (46) al rechazo social por los cambios físicos y emocionales descritos previamente (19,37,44,(46)(47)(48)(49)(50)(51). Un aspecto que marca la experiencia vivida en el TSFR es la dependencia, referida por familiares y pacientes (52)(53)(54). En todos los tratamientos, la sensación de "depender de…" limita y genera sentimientos negativos.…”
Section: Temáticas Sintetizadasunclassified
“…La síntesis de la literatura indica que los pacientes en TSFR reconocen que pierden autonomía por la dependencia al tratamiento como única forma de supervivencia (30,35,53,54), por tanto, el equipo de salud debe desarrollar intervenciones que favorezcan la recuperación de esta; una alternativa es educar a los cuidadores no formales y a los pacientes para que realicen las actividades de la vida cotidiana que les sean posibles (30), y promover aficiones que no representen actividad física intensa, como pintar o hacer manualidades (49,58,90). Otra intervención es establecer contacto con los servicios sociales para buscar la integración a la vida social y laboral (23, 39, 43).…”
Section: Síntesis De Evidencias-qunclassified